ARABIC LEARNING AT MADRASAH ALIYAH BASED ON THE 2013 CURRICULUM - Iis Susiawati; Moch. Hasyim Fanirin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
The purpose of this study was to obtain information and data about the implementation of the 2013 curriculum from the aspects of planning, implementation and evaluation as well as the factors that influence the process of implementing the 2013 curriculum at Madrasah Aliyah Nurul Hikmah Haurgeulis Indramayu.  The study was conducted in Madrasah Aliyah Nurul Hikmah Haurgeulis as a representation of madrasas that have implemented the 2013 Curriculum in learning Arabic.  This research was a field research with a qualitative approach.  Data obtained from three sources, namely observation, interviews and documentation.  The subjects of this study were the principal, the curriculum section and the tenth grade students of Madrasah Aliyah Nurul Hikmah Haurgeulis Indramayu.  The results of this study indicate that the implementation of the 2013 Curriculum at Madrasah Aliyah Nurul Hikmah Haurgeulis Indramayu, especially in learning Arabic, was still not running optimally according to the parameter criteria.  There were several factors that influence the implementation process of the 2013 Curriculum, namely teachers, students and infrastructure.